In Vitro Derivation of Functional Sertoli-Like Cells from Mouse Embryonic Stem Cells - Seol, Dong-Won (Cell Transplant, 2018)
Sertoli cells (SCs) in the mammalian testes are well known as supporting cells of spermatogenesis, but have recently become an attractive source of cell therapy because of their capacity for immune modulation and trophic effects. In order to increase their applicable efficacy, we demonstrate a novel differentiation method for mouse embryonic stem cell (ESC)-derived Sertoli-like cells (SLCs) via the intermediate mesoderm (IM). We show that IM derived from an induction of 6 days expressed markers such as Wt1, Lhx1, Pax2 and Osr1, and that a sequential induction of 6 days resulted in ESC-SLCs. The SLCs expressed their marker genes (Sf1, Sox9, Gata4, Wt1, Fshr and Scf), but the pluripotency-marker gene Oct4 was decreased. After sorting by FSHR expression, high-purity (> 90%) SLCs were collected that showed distinct characteristics of SCs such as high phagocytic and immune modulation activities as well as the expression of immune-related genes. In addition, when transplanted into the seminiferous tubule of busulfan-treated mice, SLCs re-located and were maintained in the basal region of the tubule. These results demonstrated that our robust sequential differentiation system produced functional SLCs from mouse ESCs in vitro.